Can Sounds Narrate? Prosody in Sound Poetry Performance. Issue 3 (December 2019) - Mildorf, Jarmila
Abstract : Audionarratology posits, among other things, that sound (including voices, noise and silence) contributes significantly to narrative world-making. This point is explored in this article by looking at three oral performances of a Dada sound poem: Hugo Ball's 'Karawane' (1916). While the actual verbal material is nonsensical in that the 'words' used do not exist in any language, the performances trigger associations of storyworlds purely by means of the sonic qualities given to the text. This suggests that, even though sound alone may not be enough to create narrative worlds that can easily be accessed without further explanation, they at least have the potential to facilitate narrativisation in listeners' minds. Human voices are shown to play a special role therein.